2009
DOI: 10.3201/eid1505.071299
|View full text |Cite
|
Sign up to set email alerts
|

CTX-M β-Lactamases inEscherichia colifrom Community-acquired Urinary Tract Infections, Cambodia

Abstract: Despite the recent global spread of CTX-M β-lactamases in Escherichia coli isolates from community-acquired urinary tract infections (CA-UTIs), their dissemination has been little studied in developing countries. In a 2-year prospective study, we documented the prevalence of extended-spectrum β-lactamases (ESBLs) in E. coli that were responsible for CA-UTIs in Phnom-Penh, Cambodia. Ninety-three E. coli strains were included. We observed a high prevalence of resistance to amoxicillin (88.2% of strains), cotrimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 34 publications
8
78
1
2
Order By: Relevance
“…In Cambodia, antimicrobial resistance is a growing concern which has already been documented for Neisseria gonorrhoeae [21], S. aureus [22], Salmonella [23,24], Shigella [23], and Escherichia coli [25]. Nearly 45% of the 20 S. aureus strains isolated by the Kampong Cham Hospital laboratory in 2011 were community acquiredmethicillin resistant S. aureus (MRSA) (Somary N., Personal communication, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In Cambodia, antimicrobial resistance is a growing concern which has already been documented for Neisseria gonorrhoeae [21], S. aureus [22], Salmonella [23,24], Shigella [23], and Escherichia coli [25]. Nearly 45% of the 20 S. aureus strains isolated by the Kampong Cham Hospital laboratory in 2011 were community acquiredmethicillin resistant S. aureus (MRSA) (Somary N., Personal communication, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Increasing levels of infection with extended-spectrum b-lactamase (ESBL)-producing E. coli strains have been described in Phnom Penh, the capital of Cambodia, and neighbouring countries. [7][8][9] We report the species and antimicrobial susceptibility of bacteria causing UTIs in children attending a paediatric hospital in north-west Cambodia.…”
Section: Introductionmentioning
confidence: 99%
“…The small number of samples harbored this gene, can result in this finding. Amongst 34 ESBL producing E. coli isolates from community acquired urinary tract infections in Cambodia, all were positive for bla CTX-M and negative for bla VEB and bla TEM in 26 (76.4%) of the ESBL-carrying strains was reported (29). One hundred and thirty seven E. coli (73.6%) were not ESBL producing according to PCT.…”
Section: Discussionmentioning
confidence: 99%
“…According to a French study, the prevalence of CTX-M-producing E. coli among the total number of E. coli isolates was 60.8%, and the occurrence of CTX-M-producing E. coli among ESBL-producing E. coli isolates was 39.8% (20). A polish study revealed that Most of the ESBL-producing isolates (75.7 %) had a bla CTX-M gene (29). Some studies have indicated that CTX-M-producing E. coli and K. pneumoniae have been imported from community acquired urinary tract infections into the hospital setting (27).…”
Section: Discussionmentioning
confidence: 99%